HTML5 Game Programming with enchant.js - Shimizu, Ryo.; Furukawa, Hidekazu; Fushimi, Ryohei; Tanaka, Ryo.; Kratzer, Kevin; McInnis, Brandon; Inc, enchantjs; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
HTML5 Game Programming with enchant.js gives first-time programmers of all ages the tools to turn their video game ideas into reality. A step-by-step guide to the free, open-source HTML5 and JavaScript engine enchant.js, it is ideally suited for game fans who have always wanted to make their own game but didn’t know how. It begins with the foundations of game programming and goes on to introduce advanced topics like 3D. We live in an age where smartphones and tablets have made games more ubiquitous than ever. Based around HTML5, enchant.js is ideally suited for aspiring game programmers who have always been intimidated by code. Games written using enchant.js take only a few hours to write, and can be played in a browser, iOS, and Android devices, removing the stress of programming to focus on the fun. Discover the joy of game development with enchant.js. Provides a comprehensive, easy guide to game programming through enchant.js Gives aspiring game developers a tool to realize their ideas Introduces readers to the basics of HTML5 and JavaScript programming.
Keywords: Computer games—Programming.; Software engineering; Game Development; Software Engineering/Programming and Operating Systems